Examining the Legal Standing of IKN Authority Regulations within Indonesian’s Legislation System - Harry Setya Nugraha; al Arif, M. Yasin; Fikri, Mhd Zakiul (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
This study scrutinizes the status of the regulations enacted by the Nusantara Capital City Authority (IKN Authority) within the Indonesian legislative hierarchy, based on Law Number 3 of 2022, also known as the IKN Law. A normative research approach underpins this analysis, utilizing legislative and conceptual methodologies. The investigation concludes that the IKN Law’s Article 5 paragraph 6, was drafted to accommodate all regulations formulated by the IKN Authority. These regulations, born out of the authority's attribution, hold an equivalent standing to those issued by a minister, institution, or agency at the central level given that the IKN Authority is an institution at the ministerial level. Consequently, the formulation of these regulations adheres to the rules governing central-level regulations, with the Supreme Court conducting their review. The unique aspect is the subject matter, which relates to the governance structure of the IKN Authority. Moreover, the formulation of regulations by the IKN Authority should: 1) Define the IKN entity’s position as a unique regional government entity; 2) Outline the types of regulations to be enacted; 3) Clarify the source of authority, which is attribution-based; 4) Specify its position in the hierarchy, equivalent to Regional Regulations; 5) Detail the formulation process and treatment, aligning it with the creation of regional legal products; 6) Elucidate the subject matter of the Regulatory Authority; and 7) Highlight the review process, which can be escalated to the Supreme Court.